التنبؤ باستهلاك الطاقة المتجددة في الجزائر حتى آفاق 2030 - سطاح ،مصطفى; بن رمضان ،انيسة (جامعة الوادي University of Eloued, 2024)
This study aims at forecasting renewable energy consumption in Algeria until 2030 bycomparing the Box-Jenkins and Winters Holt triple exponential smoothing methods on annual time series data of per capita renewable energy consumption from 1965 to 2022, in order to assess their accuracy in forecasting future consumption. Assessing the accuracy of the forecasts using forecast quality indicators, the results show that the Winters Holt triple exponential smoothing model provides more accurate and realistic forecasts than the Box-Jenkins method. The results also indicate that the Winters Holt tri-exponential bootstrap model is superior in providing reliable forecasts of renewable energy consumption from 2023 to 2030, contributing to the optimisation of renewable energy management strategies in Algeria and supporting future planning to meet energy demand in a sustainable and efficient manner.
Forecasting renewable energy consumption in Algeria until 2030: A comparative study between the BOX-JENKINS method and the HOLT WINTERS triple exponential smoothing.
Keywords: الطاقة المتجددة; التنبؤ; نماذج بوكس جنكينز; الاسلوب التمهيد الأسي الثلاثي ل holt winters: Renewable energy; forecasting; Box-Jenkins models; Holt Winters triple exponential smoothing method